2014
DOI: 10.3171/2013.8.jns13228
|View full text |Cite
|
Sign up to set email alerts
|

Predicting inpatient complications from cerebral aneurysm clipping: the Nationwide Inpatient Sample 2005–2009

Abstract: Object. Precise delineation of individualized risks of morbidity and mortality is crucial in decision making in cerebrovascular neurosurgery. The authors attempted to create a predictive model of complications in patients undergoing cerebral aneurysm clipping (CAC).Methods. The authors performed a retrospective cohort study of patients who had undergone CAC in the period from 2005 to 2009 and were registered in the Nationwide Inpatient Sample (NIS) database. A model for outcome prediction based on preoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 18 publications
0
36
1
Order By: Relevance
“…Although LOS is a major target for cost containment, the focus should be only on excessively lengthy hospitalizations not justified by patient comorbidities. The comorbidities associated with increased LOS, in the setting of CAC, have been identified in prior studies, 19 and should be taken into account to avoid penalizing the care of sicker patients. Other important contributors to increased LOS, and subsequently higher hospitalization costs are patient safety indicators, and hospital acquired conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Although LOS is a major target for cost containment, the focus should be only on excessively lengthy hospitalizations not justified by patient comorbidities. The comorbidities associated with increased LOS, in the setting of CAC, have been identified in prior studies, 19 and should be taken into account to avoid penalizing the care of sicker patients. Other important contributors to increased LOS, and subsequently higher hospitalization costs are patient safety indicators, and hospital acquired conditions.…”
Section: Discussionmentioning
confidence: 99%
“…3,34 Despite initial criticism about the study’s design and limited focus, further national investigations 4,5,8,9,13,17,22 and a North American trial 29 confirmed its findings. These results have fueled an explosive growth of coiling in this population.…”
Section: Introductionmentioning
confidence: 94%
“…Patients harboring wide necked aneurysms traditionally pose a higher risk of treatment with endovascular therapy due to the requirement for an adjuvant device. This can be particularly challenging in patients with ruptured cerebral aneurysms in whom microsurgical clipping may be a technical challenge either due to the location of the aneurysm or neurological status of the patient 2. Although stents have been implanted in ruptured aneurysms, there appears to be a high incidence of hemorrhagic complications due to the need for dual antiplatelet agents 3.…”
Section: Introductionmentioning
confidence: 99%